Size-dependent gender gaps in entrepreneurship: The case of Chile - David Cuberes; Marc Teignier (Latin American Economic Review, 2022)
This paper documents differences in firm size depending on whether their manager is a man or a woman and studies the aggregate implications of these gender gaps in Chile. We document that in 2007 less than a quarter of firms are managed by women and that this gap takes its largest value for managers with tertiary education or more. In terms of their number of workers, female-run firms are on average about three times smaller than those run by men. Moreover, the ratio of men to women managers is always above one, but it is much higher for large and medium firms than for small or micro ones. These differences remain significant after controlling for several manager and firm characteristics. We then use an extended version of the theoretical framework developed in Cuberes and Teignier (2016) to incorporate these facts and obtain quantitative predictions about their effects on aggregate productivity and income in Chile. We find that the observed gender gaps in entrepreneurship in Chile generate a fall in aggregate productivity and aggregate income of 7.5%.
Keywords: E2; J21; J24; O40; 330; gender inequality; aggregate productivity; firm size; talent misallocation